Hemocyte classification of three mosquito vectors: Aedes togoi, anopheles lesteri and culex quinquefasciatus - W. Dedkhad (2019)
© 2019, Malaysian Society for Parasitology. All rights reserved. Insect blood cells or hemocytes play an important role in the defense against parasites and other pathogenic organisms. However, the hemocyte types of three mosquito vectors, Aedes togoi, Anopheles lesteri and Culex quinquefasiatus are not well known. Therefore, the aim of this study was to characterize the hemocytes of these three mosquito species based on morphology using light microscopy. The abdominal cutting and perfusion method was used in this study as it took the fewest steps, provided the largest number of hemocytes and yielded less contamination with fat body cells. Hemocyte typing, based on morphology, revealed three types of hemocytes (prohemocytes, oenocytoids and granulocytes) that were contained in the hemolymph of all three mosquito species. This study demonstrated that the use of distinct morphology with light microscopy provided sufficient criteria to characterize and differentiate mosquito hemocytes. This technique will be useful in terms of cost saving and for new researchers who begin to study in this field.